RELATIONSHIP BETWEEN THE PREVALENCE OF METABOLIC SYNDROME AND NON-PHARMACOLOGICAL TREATMENT: PHYSICAL EXERCISE AND FOOD PROFILE (Fiep Bulletin - online, 2011)
The metabolic syndrome (MS) is a clustering of cardiovascular risk factors including diabetes, obesity, dyslipidemia and hypertension. The present study aimed to relate the prevalence of metabolic syndrome with non-pharmacological treatment in patients in the Outpatient Nutrition of the University Hospital Lauro Wanderley from Federal University of Paraíba-João Pessoa / PB. This is a cross-sectional study and descriptive. As a result, from the 62 patients treated between November-December 2009 (average age 39.58 ± 12.57 years), 30 of them had metabolic syndrome representing an overall prevalence of 48.39%. Regarding nutritional status, 13.34% (4) shown to be eutrophic, 23.33% (7) overweight, and 63.33% (19) were obese. As for non-pharmacological treatment (physical exercise and dietary profile) was found that 53.34% (16) of the patients practiced physical exercise. And when it comes to food profile of macronutrients, 60% (18) of the patients had unbalanced diet, predominating consumption of foods rich in simple carbohydrates and fats, especially saturated ones.
Keywords: metabolic syndrome; diet and physical exercise